For the Love of Cinema: history, chronicle and memory in the Invention of certain look - Lucena Lucas, Meize Regina (2012)
This article analyzes the uses of the concept of history in the context of building a new cinema culture in Brazil in the 1950's. During this period, a evaluation time of Brazilian cinema considered in many aspects, there were many meetings about cinema and publishing theoretical magazines and history books, took place the literary supplements and film archives in Rio de Janeiro and Sao Paulo, it grows the movie clubs, it formed public collections and expand the private sector. The existence of material conditions for the realization of a history of Brazilian cinema is directly related to the construction of a new look at the movies: more independent of foreign standards and facing a reflection on the aesthetics.